2015
DOI: 10.1063/1.4916304
|View full text |Cite
|
Sign up to set email alerts
|

Morin transition temperature in (0001)-oriented α-Fe2O3 thin film and effect of Ir doping

Abstract: The structural properties and Morin transition in c-plane-oriented α-Fe2O3 and Ir-doped α-Fe2O3 thin films have been investigated. The enhancement of the Morin transition temperature (TM) in α-Fe2O3 film by Ir doping has been demonstrated. The TM in the c-plane-oriented α-Fe2O3 thin film was determined from the temperature-dependent in-plane magnetization and change of coercivity (Hc); this TM value was found close to that of bulk α-Fe2O3. The spin directions of non-doped and Ir-doped α-Fe2O3 at room temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
34
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 17 publications
3
34
2
Order By: Relevance
“…The magnetization hysteresis curves measured with a SQUID magnetometer at 300 K are illustrated in Fig. 1c, which show a small Ms around 1.5~2 emu/cc and a coercive field of 500~1000 Oe within the entire thickness range (10~120 nm), consistent with the reported values in previous literatures 18,19 . In order to study current-induced switching and observe the SMR, we sputter 5 nm Pt on 10 nm α-Fe2O3 films and fabricate Hall bars with 4~20 μm width ( Fig.…”
supporting
confidence: 88%
“…The magnetization hysteresis curves measured with a SQUID magnetometer at 300 K are illustrated in Fig. 1c, which show a small Ms around 1.5~2 emu/cc and a coercive field of 500~1000 Oe within the entire thickness range (10~120 nm), consistent with the reported values in previous literatures 18,19 . In order to study current-induced switching and observe the SMR, we sputter 5 nm Pt on 10 nm α-Fe2O3 films and fabricate Hall bars with 4~20 μm width ( Fig.…”
supporting
confidence: 88%
“…Moreover, these samples were post annealed at 973 K in air for one day. In contrast, our previous report shows we could successfully observed T SR in (0001) oriented α‐Fe 2 O 3 film and T SR can be enhanced above 400 K by Ir doping , without post annealing of the sample. Pressure induced change in spin‐reorientation transition temperature also has been reported around 3.7 ± 0.2 K kbar −1 for both single crystal and powder samples .…”
Section: Introductioncontrasting
confidence: 93%
“…Below T SR , | K FS | > | K MD |, and the spin direction is perpendicular while above T SR , | K MD | > | K FS | and the spin direction is in‐plane. In our earlier report, we demonstrated the suppression of SRT by Ir doping which can enhance spin‐orbit interaction resulting in the enhancement of K FS . Epitaxial α‐Fe 2 O 3 films on Al 2 O 3 substrates have spin‐reorienation transition temperatures that depend on the crystal orientation .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Consequently, reversible engineering of the anisotropy, and thereby the Morin transition, is crucial as it would allow control over magnon-transport 20,21 and topological texture dimensions 22 . Previous reports have shown that strain 25 , chemical doping 19,[26][27][28][29][30] and meso-structure 31 can modify the antiferromagnetism in α-Fe 2 O 3 . However, lack of reversibility and scalability makes these approaches difficult to exploit in practical applications.…”
mentioning
confidence: 97%